Strategi Pengembangan Komunikasi Massa Dalam Mendukung Pembangunan Pertanian Dengan Pendekatan Jati Diri Bangsa Yang Berorientasi Pada Budaya - Cahyono Tri Wibowo; Sumardjo .; D. Hafidhuddin; S. S Agung (Jurnal Komunikasi Pembangunan, 2011)
Abstract The results of  analysis about  the nation'smorality decline causes by  lack of filteringtheinterferenational culture morality, the nation's culturaldamage, and lack of the educationalmode forthe communitycharacter.  Condition ofthe nation's culturaldamage causes by the influences offoreignculture  (Westernization),  lack of  educationand  theunderstanding and practising of religion, and lack of preservation ofthe nation'snoblecultural values.  The effects of  that causes are the national identity decline and  lack ofcommunity participationin supportingagricultural development, and  the end  is  lessdevelopment ofmass communicationsin supportingagricultural developmentwiththe nation'sidentity approach based on  the culture orientation.The improvement of Indonesia nation’s  moralitycan be done by the establishment and enforcement  of govermentpoliciesare neededin order tofilter thenation's culture,  keepingthe noble values ​​ofnational culture, and increasing the charactereducation/nation’s character.  Keepingthe noble values ​​ofnational culture can  be done by promoting the valuable of nation's culturalvalues,  practices thereligiousvalues​​into real action, and continuous the preservingnational culture and monitoring ofthatactivities. If the moralityof Indonesia nations is improved  then communityparticipation increased and  the national identity is more solid, the last societyhasan activeparticipationinthe development ofmasscommunicationwiththe nation'sidentity approach that oriented to theculture of Indonesia. Key words: fixed the Indonesia nation’s morality